Influence of tobacco and e-cig smoke on intestinal microbiota: a systematic review. (30th September 2020) - Giffi, M; Antinozzi, M; Sini, N; Valeriani, F; Gallè, F; Romano Spica, V; Liguori, G; De Vito, C; Cattaruzza, M S
Abstract: Background: Intestinal microbiota (IM) plays a crucial role in maintaining human body homeostasis, yet it is highly susceptible to lifestyle changes and environmental factors, such as tobacco and e-cig smoking. This systematic review aims to investigate the relationship between smoking and IM in healthy humans, by assessing abundance of Phyla and species' variability. Methods: PubMed, Scopus and Web of Science were searched until April 2019. Studies assessing IM of healthy adult tobacco/e-cig smokers, collected on faecal samples and analysed with genome sequencing of rRNA 16 S, were included. Any type of study design, described in English, was considered. Quality assessment was performed with Methodological index for non-randomized studies and Joanna Briggs Institute Critical Appraisal tool for cross-sectional studies. Results: Eight out of 1, 838 studies (one controlled prospective and seven cross-sectional studies) were included. The only controlled prospective study found a signiﬁcant increase in α and β-diversity, an increase in Firmicutes (p = 0.014) and a decrease in Bacteroidetes (p = 0.019) after a smoking cessation intervention. In cross- sectional studies, ﬁve out of seven studies found a statistically signiﬁcant decrease in α-diversity among tobacco/e-cig smokers, while results on β-diversity were more contradictory. One out of two studies evaluating Firmicutes found a signiﬁcant decrease in smokers (p = 0.047). The only study assessing Bacteroidetes found a signiﬁcant increase among smokers (p = 0.015). Five studies analysed genera, three of them found a decrease in Bacteroides and two an increase in Prevotella. Conclusions: What seems to emerge is a decreasing species' variability in smokers, yet it is difficult to proﬁle IM in smokers in terms of phyla's abundance, because of few studies available and some further limitations, such as small sample sizes and lack of adjusted analysis to cope with confounding factors like gender, diet and other lifestyles. Key messages: There is a decrease in species' variability among smokers. Further studies are needed to assess abundance of phyla in healthy smokers, taking into account confounding factors.